Online Purchases on Social Commerce TikTok: Within Content Marketing and Live Streaming Triggers - Lukas Arturito; Siti Nurlaelatul Jannah; H. Misbak; Tiara Muthiarsih (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the influence of video content and live streaming on quick online purchasing decisions in social commerce. A quantitative method was used, involving 100 respondents who were purposively selected through an online questionnaire using Google Forms. The results of the study show that both variables have a positive and significant influence with a moderate level of influence on purchasing decisions. Video content serves as an entry point that helps consumers in the product consideration stage, while real-time interaction, such as live streaming, can directly address consumer doubts and accelerate decision-making through high responsiveness and interactivity. These findings emphasize the importance of sustained audience engagement and relationship building before, during, and after transactions. In conclusion, the success of marketing in social commerce does not only depend on product quality and brand reputation but also on adaptive and authentic communication strategies, with content that can communicate independently and hosts who are active and sincere in interacting with the audience. This study suggests that brands prioritize interactive experiences and relevant content to enhance instant purchasing decisions in a competitive e-commerce environment.